2014
DOI: 10.5194/bg-11-1627-2014
|View full text |Cite
|
Sign up to set email alerts
|

NEP of a Swiss subalpine forest is significantly driven not only by current but also by previous year's weather

Abstract: Abstract. Understanding the response of forest net ecosystem productivity (NEP) to environmental drivers under climate change is highly relevant for predictions of annual forest carbon (C) flux budgets. Modeling annual forest NEP with soil-vegetation-atmosphere transfer models (SVATs), however, remains challenging due to unknown delayed responses to weather of the previous year. In this study, we addressed the influence of previous year's weather on the interannual variability of NEP for a subalpine spruce for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 45 publications
3
28
0
1
Order By: Relevance
“…Since the forest ecosystem shows a pronounced phenological cycle, estimated GPP are likely to be overestimated. In fact, Zielis et al [100] and Wolf et al [101] report maximum GPP values of 5 g C m −2 day −1 for a Norway spruce forest close to Davos, Switzerland, that is comparable to our observation taken at the peak season. Scaling their flux tower-based GPP estimates to annual values results in roughly 1000 g C m −2 year −1 , while we observed average values of 1255 ± 342 g C m −2 year −1 , confirming the expected overestimation of GPP when using a single snapshot in combination with the EVI approach.…”
Section: Reliability Of Forest Productivity Retrievalsupporting
confidence: 91%
“…Since the forest ecosystem shows a pronounced phenological cycle, estimated GPP are likely to be overestimated. In fact, Zielis et al [100] and Wolf et al [101] report maximum GPP values of 5 g C m −2 day −1 for a Norway spruce forest close to Davos, Switzerland, that is comparable to our observation taken at the peak season. Scaling their flux tower-based GPP estimates to annual values results in roughly 1000 g C m −2 year −1 , while we observed average values of 1255 ± 342 g C m −2 year −1 , confirming the expected overestimation of GPP when using a single snapshot in combination with the EVI approach.…”
Section: Reliability Of Forest Productivity Retrievalsupporting
confidence: 91%
“…Recent studies have also suggested that lagged effects can significantly affect annual GPP (Gough et al, 2008;Marcolla et al, 2011). For example, Zielis et al (2014) used long-term eddy covariance data collected at a spruce forest site to show that inclusion of meteorological data from the previous year significantly improved estimates of net ecosystem exchange, suggesting that next generation models need to include lagged effects and functional responses to climate forcing in previous years.…”
Section: Interannual Variation In Gppmentioning
confidence: 99%
“…2001; Pilegaard et al, 2001;Kolari et al, 2004;Zielis et al, 2014;Danielewska et al, 2015). Furthermore, according to comprehensive quantification of the C balance of different forests, using EC and biometric measurements, temperate evergreen forests sequester from 133 ± 47 up to 389 ± 42 g C m −2 y −1 depending on climatic conditions (Luyssaert et al, 2007).…”
Section: Introductionmentioning
confidence: 99%